Sistema de aquisição de dados e controle de plantas descentralizadas de energias renováveis - Brito, Fábio Timbó (2011)
The contribution of renewable energy in world energy production is increasing rapidly. In Brazil, the installed capacity of wind power reached 1 GW in May 2011 and the investments for projects with start-up until 2013 are R$ 25 billion. Data acquisition systems are essential to estimate the energy potential of renewable energy plants, the wind power production as an example, require a large volume of data available from past years in order to derive accurate models of the renewable energy. In a similar way, if the photovoltaic generation system is installed in a place of a low solar potential, the project is unable to repay the value of the investment. Therewith, the development of a data acquisition system for decentralized renewable energy sources monitoring is described in the present dissertation. The system has a microcontroller-based unit for local storing and data transmission to internet by a modem and a database server is used to store the data. The proposed architecture is easily extended for controlling a decentralized renewable energy plant by the Matlab/Simulink program. A practical implementation is presented with the utilization of a non-recursive least square algorithm estimator to estimate the transfer function of a pumping plant and allowing an accurate control of water flow by the use of a PI controller. Correlations and performance tests are used to compare the data collected by the system prototype with the data collected by commercial equipment. The results indicate that the root mean square error is 0.103 m/s, for wind speed measurement and the correlation factor is greater than 0.9996. Overall, the low errors rates indicate that the data have been stored on to a broadly similar form to what would be expected based in a commercial equipment. Finally, the possibility of a commercial use of this project is presented to improvement of data transmission efficiency in a meteorological tower of Petrobrás in Paracuru - CE, Brasil.